2018
DOI: 10.1111/ene.13628
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin‐sensitive magnetic resonance imaging features of the substantia nigra and locus coeruleus in de novo Parkinson's disease and its phenotypes

Abstract: Substantia nigra pars compacta neuromelanin changes occur across both motor and non-motor (with and without depressive symptoms) subtypes, whilst LC changes are more notable in PD patients with depressive symptoms. Our results may provide new evidence to understand the pathophysiology of non-motor symptoms in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 41 publications
(52 reference statements)
13
72
1
Order By: Relevance
“…and Y.F.) was 0.833 for the average CNR of the LC, indicating good to excellent intra‐ and interrater agreement of LC measurements, consistent with our previous report …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…and Y.F.) was 0.833 for the average CNR of the LC, indicating good to excellent intra‐ and interrater agreement of LC measurements, consistent with our previous report …”
Section: Methodssupporting
confidence: 91%
“…All NM‐MR images were transferred to a workstation (ADW 4.6; GE Healthcare) for analysis, according to our previous study . One of the authors (a neuroradiologist with 10 years of experience [W.J.…”
Section: Methodsmentioning
confidence: 99%
“…We did not demonstrate any differences in SI norm between the two groups; however, several studies show a decreased SI SN in patients with PD compared to HC [18][19][20][21][22][23][24][25][26][27][28]. We might fail to demonstrate any difference in SI norm due to the small sample size.…”
Section: Discussioncontrasting
confidence: 81%
“…In 1986, Duguid et al [17] observed a reduced width of SN pars compacta in patients with PD using a 1.5T scanner. Since then, several MR studies report a decrease in signal intensity [18][19][20][21][22][23][24][25][26][27][28] and volume or surface reduction [19,21,22,25,26,[28][29][30][31][32][33][34] of the SN in patients with PD. Moreover, discrimination between PD patients and other Parkinsonian syndromes also yields reliable results [29,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Although in vivo positron emission tomography imaging studies using non-specific ligands failed to identify the noradrenergic damage, more recent neuromelanin-sensitive magnetic resonance studies have found progressive loss of the LC signal in both idiopathic and genetic PD patients and even a lower signal in those PD patients with depressive symptoms (Sasaki et al, 2006;Castellanos et al, 2015;Schwarz et al, 2017;Wang et al, 2018). 18 F-dopa positron emission tomography imaging, as an index of monoaminergic nerve terminal function, have also demonstrated a reduced uptake in the LC, indicating progressive loss of noradrenergic terminal function (Pavese et al, 2011).…”
Section: Clinical Evidencementioning
confidence: 99%